Flashback - Universiti Malaysia Pahang in the past, present and future - Irene, Wei Kiong Ting (2019)
Universiti Malaysia Pahang (UMP) has been on the run in achieving continuous excellences amidst the dynamically challenging environment since it was established as a public technical university by the Malaysian government on 16 February 2002. Certainly, UMP celebrated another milestone anniversary last month, marking a closer step in fulfilling its vision to be a distinguished technological university. UMP has been the leader within the Malaysian Technical University Network (MTUN), which is made up of four technological universities in Malaysia though.